Periplocymarin Alleviates Doxorubicin-Induced Heart Failure and Excessive Accumulation of Ceramides - Yun, Weijing; Qian, Lei; Yuan, Ruqiang; Xu, Hu (Frontiers in Cardiovascular Medicine, 2021)
Doxorubicin (DOX)-driven cardiotoxicity could result in dilated cardiomyopathy and heart failure (HF). Previously, we showed that periplocymarin exerted cardiotonic role by promoting calcium influx and attenuated myocardial fibrosis induced by isoproterenol (ISO) by improving cardiomyocytes metabolism. However, the impact of periplocymarin on DOX-triggered cardiomyopathy has not been investigated. In the current study, C57BL/6 mice were randomly divided into three groups, namely control, DOX and DOX+ periplocymarin group. Cardiac function and apoptosis were measured. Our results revealed that periplocymarin administration greatly improved DOX-induced cardiac dysfunction manifested by EF%, FS%, LVAW, LVPW, LV mass, and attenuated DOX-induced cardiomyocyte apoptosis assessed by H&E staining, TUNEL staining and western blotting. Further study using H9c2 cells revealed that pretreatment of periplocymarin suppressed DOX-induced apoptosis evidenced by annexin V staining. Moreover, LC-MS/MS analysis demonstrated that DOX lead to an accumulation in serum ceramide, and pre-treatment of periplocymarin could reverse this phenomenon. Network pharmacology also demonstrated that ceramide metabolism is involved in the process. Consistently, real-time PCR showed that periplocymarin significantly abolished the induction of the genes involved in the de novo synthesis of ceramide, i.e., CerS2, CerS4, CerS5 and CerS6, the induction was attribute to the treatment of DOX. Collectively, these results suggested that periplocymarin reduced cardiomyocyte apoptosis to protect hearts from DOX-induced cardiotoxicity and the de novo synthesis of ceramides was involved in this process.